2012
DOI: 10.3171/2012.8.peds12139
|View full text |Cite
|
Sign up to set email alerts
|

Response to acute concussive injury in soccer players: is gender a modifying factor?

Abstract: Object Several studies have suggested a gender difference in response to sports-related concussion (SRC). The Concussion in Sport group did not include gender as a modifying factor in SRC, concluding that the evidence at that point was equivocal. In the present study the authors endeavored to assess acute neurocognitive and symptom responses to an SRC in equivalent cohorts of male and female soccer players. The authors hypothesized that female athletes would experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 27 publications
2
49
2
Order By: Relevance
“…The results of several recent studies of sex effects on cognition and symptoms in SRC lead to the preliminary conclusion that symptoms rather than neurocognitive scores appear to be the main driver of sex disparities in the sequelae of SRCs. 4,7,12,13,44 The etiology of this disparity is outside the scope of our study; however, male athletes have been shown to minimize or deny symptoms to avoid removal from a game or practice, whereas female athletes show more concern for their future health. [13][14][15]17,24 Embedded social biases may be at the heart of symptom variation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of several recent studies of sex effects on cognition and symptoms in SRC lead to the preliminary conclusion that symptoms rather than neurocognitive scores appear to be the main driver of sex disparities in the sequelae of SRCs. 4,7,12,13,44 The etiology of this disparity is outside the scope of our study; however, male athletes have been shown to minimize or deny symptoms to avoid removal from a game or practice, whereas female athletes show more concern for their future health. [13][14][15]17,24 Embedded social biases may be at the heart of symptom variation.…”
Section: Discussionmentioning
confidence: 93%
“…Although authors have found disparities in male and female neurocognitive scores at baseline 3,6,15,43 and postconcussion, 4,12,14 a recent study evaluated a homogeneous group of male versus female soccer players and found no differences in neurocognitive deficits after SRC. 44 With respect to symptoms, prior studies have shown different symptom profiles for females and an increased number of symptoms at baseline and postconcussion. Although our study failed to replicate major symptom differences, we did confirm a higher level of symptom endorsement and longer return to baseline in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the literature on differential reporting of the number, type, or severity of concussion symptoms by sex remain mixed, [13][14][15][16][17][18][19] and there is a paucity of information on whether agreement levels for reporting sports-related events by athletes and key persons is different between female and male players. In terms of the type of activity, football has historically been the main sport in which serious concerns about concussion have been raised.…”
Section: Introductionmentioning
confidence: 99%
“…Since most sports injuries occur as a result of the interaction of intrinsic and extrinsic risk factors, they both represent a valid scope of research. However, intrinsic risk factors can be almost completely monitored by having an insight into the musculoskeletal potential of a person, his or her functional status as well as all other available anthropological parameters (Venturelli, Schena, Zanolla, & Bishop, 2011;Volpi & Taioli, 2012;Zuckerman, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additional group of intrinsic risk factors are athlete's psychological features such as motivation, aggressiveness, perception of risk situation and willingness to accept risk. Extrinsic risk factors can be associated with a certain sport activity such as type, intensity and frequency of training sessions, warmth, humidity or coldness of weather, special equipment, or type of surface the activity is practised on (van Beijsterveldt, et al, 2011(van Beijsterveldt, et al, , 2012Zuckerman, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%